A Built-In Self-Test Structure (BIST) for Resistive RAMs characterization: Application to bipolar OxRRAM. (January 2015) - Aziza, H.; Bocquet, M.; Moreau, M.; Portal, J-M.
Highlights: The BIST structure collects ON/OFF resistance distributions for reliability assessment of ReRAM. The BIST structure is based on a modification of the sense amplifier architecture. The BIST is common to the entire memory array, which reduces the area overhead. The test time overhead is low as only the read operation of the memory is modified. Abstract: Resistive Random Access Memory (RRAM) is a form of nonvolatile storage that operates by changing the resistance of a specially formulated solid dielectric material[1] . Among RRAMs, oxide-based Resistive RAMs (so-called OxRRAMs) are promising candidates due their compatibility with CMOS processes and high ON/OFF resistance ratio. Common problems with OxRRAM are related to high variability in operating conditions and low yield. OxRRAM variability mainly impact ON/OFF resistance ratio. This ratio is a key parameter to determine the overall performance of an OxRRAM memory. In this context, the presented built-in structure allows collecting statistical data related to the OxRRAM memory array (ON/OFF resistance distributions) for reliability assessment of the technology.